PERAN PERCEIVED STRESS DAN SELF-EFFICACY TERHADAP TEACHER BURNOUT GURU TK PADA MASA PANDEMI COVID-19 - Supi Catur Nadyastuti; Heni Mularsih (Almh); Sri Tiatri (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
This study aims to determine whether there is a role for perceived stress and self-efficacy on kindergarten teacher burnout in Jakarta during the Covid-19 pandemic. This research uses a quantitative approach and multiple linear regression analysis. This study uses the MBI-ES (Maslach Burnout Inventory-Educators Survey) measuring instrument developed by Maslach and Jackson (1996) to measure teacher burnout, and the PSS (Perceived Stress Scale) measurement tool developed by Cohen (1983) is used to measure perceived stress. Meanwhile, to measure teachers' self-efficacy against teacher burnout, the GSES (General Self-Efficacy Scale) measurement tool was used which was built following Bandura's social cognitive theory (Bandura, 1997), developed by Schwarzer and Jerusalem, 1995. The subjects of this study were 362 teachers from public and private kindergartens in Jakarta. The results of this study have a very significant relationship between perceived stress and self-efficacy variables on teacher burnout of kindergarten teachers in Jakarta during the Covid-19 pandemic. p = 0.000 (p <0.01). The R square is 0.927 which when proxied (0.927 x 100% = 92.7%) means that the amount of perceived  stress and self-efficacy towards teacher burnout was 92.7% and the remaining 7.3% was influenced by other factors not examined in this study.  Penelitian ini bertujuan untuk mengetahui apakah ada peran perceived stress dan self-efficacy terhadap teacher burnout guru TK di Jakarta pada masa pandemi Covid-19. Penelitian ini menggunakan pendekatan kuantitatif dan analisis regresi linear berganda. Menggunakan alat ukur MBI-ES (Maslach Burnout Inventory-Educators Survey) yang dikembangkan oleh Maslach dan Jackson (1996) untuk mengukur teacher burnout, dan alat ukur PSS (Perceived Stress Scale) yang dikembangkan oleh Cohen (1983) untuk pengukuran perceived stress. Sedangkan untuk mengukur self-efficacy terhadap teacher burnout digunakan alat ukur GSES (General Self-Efficacy Scale) yang dibangun mengikuti teori kognitif sosial Bandura (Bandura, 1995), dikembangkan oleh Schwarzer dan Jerusalem (1995). Subjek penelitian ini adalah 362 guru dari TK Negeri dan Swasta di Jakarta. Hasil dari penelitian ini terdapat hubungan yang sangat signifikan antar variabel perceived stress dan self efficacy terhadap teacher burnout guru TK di Jakarta pada masa pandemi Covid-19. Hal tersebut ditunjukkan dengan diperoleh nilai F = 2264,757 dengan p = 0,000 (p<0,05). R square sebesar 0,927 yang apabila dipresentasikan (0,927 x 100% = 92,7%) artinya besar sumbangan perceived stress dan self-efficacy terhadap teacher burnout sebesar 92,7% dan sisanya 7,3% dipengaruhi oleh faktor lain yang tidak diteliti dalam penelitian ini.